Urban Planning and Sustainable Land Use (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint gathers the literature regarding diverse disciplines within the context of contemporary urban planning and land use in different regions to address global challenges in sustainable urban development.